Analisis Faktor-Faktor E-Service Quality Kalbisphere pada Kepuasan Mahasiswa Kalbis Institute - Halawa, Fransiscus Amonio; Fensi, Fabianus (Universitas Bunda Mulia, 2019)
This research was conducted to find out whether there were influences of E-Service Quality factors on student satisfaction. The objects of research in this study were the Active Students of Kalbis Institute in 2017, IT Department with 35 people. The variable used in this study is E-Service Quality and Student Satisfaction, the E-Service Quality variable is denoted as X variable, while the Student Satisfaction variable is denoted as variable Y. The data obtained was analyzed using multiple linear regression. The results of the study show that Responsiveness, Contact, Efficiency, System Availability, and Privacy have no partial significant effect on student satisfaction, while the Compensation and Fullfilment variables have a partially significant effect on student satisfaction. Based on the results of the F test, it can be seen that simultaneously Contact, Efficiency, System Availability, Fullfillment, and Privacy have a significant effect on student satisfaction. According to the author's observation, Kalbisphere faces several problems, therefore it is necessary to improve the quality of Kalbisphere so that students feel more satisfied with the future Kalbisphere services. Keywords : E-Service Quality, Student satisfaction, Kalbisphere